Deterministic reservoir computing for chaotic time series prediction - Johannes Viehweg; Constanze Poll; Patrick Mäder (Scientific Reports)
Abstract Reservoir Computing was shown in recent years to be useful as efficient to learn networks in the field of time series tasks. Their randomized initialization, a computational benefit, results in drawbacks in theoretical analysis of large random graphs, because of which deterministic variations are still an open field of research. Building upon Next Generation Reservoir Computing and the Temporal Convolution Derived Reservoir Computing, we propose a deterministic alternative to the higher-dimensional mapping therein, TCRC-LM and TCRC-CM, utilizing the parameterized but deterministic Logistic mapping and Chebyshev maps. To further enhance the predictive capabilities in the task of time series forecasting, we propose the novel utilization of the Lobachevsky function as non-linear activation function. As a result, we observe a new, fully deterministic network being able to outperform TCRCs and classical Reservoir Computing in the form of the prominent Echo State Networks by up to $$99.99%$$ 99.99 % for the non-chaotic time series and $$87.13%$$ 87.13 % for the chaotic ones.